2023
DOI: 10.1021/acs.jpclett.3c01264
|View full text |Cite
|
Sign up to set email alerts
|

Lone Pair Electrons with Weak Nuclear Binding Inducing Sensitive Nonlinear Optical Responses in Phosphorus Clusters

Abstract: Phosphorus clusters have broadband optical responses, adjustable geometries, and electronic structures, potentially balancing transparency and nonlinearity. In this study, the optical properties of phosphorus clusters are analyzed by using first-principles calculations. Phosphorus clusters exhibit strong light absorption in the ultraviolet region while remaining transparent in the visible to far-infrared bands. Importantly, the third-order nonlinear optical performance of phosphorus clusters surpasses that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A previous study has demonstrated that weak nucleus-bound lone-pair electrons induce sensitive optical responses in clusters. 27 The nuclear binding strength of lone-pair electrons gradually strengthens from silicon to sulfur clusters, offsetting the advantage offered by the number of lone-pair electrons and explaining the observed phenomenon. Compared to silicon and phosphorus clusters, which have LAR values of no more than one, sulfur clusters possess more abundant lone-pair electrons with LAR values of two.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has demonstrated that weak nucleus-bound lone-pair electrons induce sensitive optical responses in clusters. 27 The nuclear binding strength of lone-pair electrons gradually strengthens from silicon to sulfur clusters, offsetting the advantage offered by the number of lone-pair electrons and explaining the observed phenomenon. Compared to silicon and phosphorus clusters, which have LAR values of no more than one, sulfur clusters possess more abundant lone-pair electrons with LAR values of two.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic structure analyses, (hyper)polarizability density maps, and molecular orbital localization techniques were used to analyze the linear and nonlinear optical responses of silicon clusters. Particularly, thorough comparisons between the results obtained for silicon clusters and those for phosphorus and sulfur clusters, which the author has previously studied, 27,28 were conducted. These analyses yielded valuable insights into the size-dependent optical response behaviors of silicon clusters.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that the nuclear binding strength to lone-pair electrons has an important impact on the nonlinear optical responses. 25 The lone-pair electrons of sulfur atoms are more strongly bound by the nucleus than those of phosphorus atoms because of the larger atomic radius, which negates the numerical advantage of lone-pair electrons of sulfur clusters, making the nonlinear responses less sensitive. Using an external electric field to tune the nuclear binding strength of the lone-pair electrons is expected to improve considerably the third-order nonlinear optical responses of sulfur clusters.…”
Section: Resultsmentioning
confidence: 99%
“…24 Recently, I demonstrated that the polarization of lone-pair electrons induces sensitive nonlinear optical responses, which mainly emerge in nonmetal atoms with larger radii. 25 For example, phosphorus clusters exhibit sensitive nonlinear optical responses, superior to p -nitroaniline with a D–π–A structure. The SCALP effect primarily enhances the second-order nonlinear optical effects, while the polarization of lone-pair electrons helps to improve the third-order nonlinear optical responses in medium.…”
Section: Introductionmentioning
confidence: 99%